The adaptation strategies of English loanwords among Kelantan Malay dialect speakers - Sakinah Nik Muhamad Naziman; Sharifah Raihan Syed Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper discusses the adaptation strategies when the Kelantan dialect speakers borrow words from English. It also discusses the findings for loanwords approach. There are three approaches to account for the adaptation and processing of sound-based loanwords namely Perception, Phonology or Perception-Phonology Approaches. In order to examine and determine which approach of adaption can satisfactorily account for the adaptation processes in the Kelantan dialect of Malay, the source of input is examined. Data for this research were obtained from two sources: a previous study from Shapri (1980) and observations which were carried out in Kota Bharu, Kelantan. There were 113 and 55 words from Shapri (1980) and from observation, respectively, as used for this study. Data analysis shows that four adaptation strategies were applied in the Kelantan dialect of Malay. These are consonant substitution, consonant deletion, debuccalisation, vowel epenthesis and final consonant clusters simplification. Considering the source of input and the adaptation strategies, the adaptation process in Kelantan Malay dialect is mostly phonological. Hence, this proves that the phonological Approach could better explain how English loanwords are processed in the Kelantan Malay dialect. The discussion on English loanword adaptation strategies has its implications to Malay grammar and future phonological theory. Some phonological patterns occur in the Kelantan Malay dialect whereas they are not formally stated and have never been discussed in the phonological system of the dialect.